Virtual rehabilitation: what are the practical barriers for home-based research? - Threapleton, Kate; Drummond, Avril E.R.; Standen, Penny (SAGE Journals, 2016)
Virtual reality technologies are becoming increasingly accessible and affordable to deliver, and consequently the interest in applying virtual reality within rehabilitation is growing. This has resulted in the emergence of research exploring the utility of virtual reality and interactive video gaming interventions for home use by patients. The aim of this paper is to highlight the practical factors and difficulties that may be encountered in research in this area, and to make recommendations for addressing these. Whilst this paper focuses on examples drawn mainly from stroke rehabilitation research, many of the issues raised are relevant to other conditions where virtual reality approaches have the potential to be applied to home-based rehabilitation.